An Intimate Relationship Between Eriophyoid Mites and Their Host Plants – A Review - de Lillo, Enrico; Pozzebon, Alberto; Valenzano, Domenico; Duso, Carlo (Frontiers in Plant Science, 2018)
Eriophyoids (Acari Eriophyoidea) provide an excellent example of intimate and not destructive relationships between plants and their arthropod feeders. These mites are associated with annual and perennial plants including ferns, and are highly specialized with a dominant monophagy. This paper is aimed at critically reviewing knowledge on eriophyoids of economic importance. They can be found within all the ecological classes (vagrant, gall-making and refuge-seeking species) and some of them are vectors of plant viruses. Eriophyoid-host plant interactions, the susceptibility within selected crops and main host plant tolerance/resistance mechanisms are discussed. Fundamental concepts, subjects, and problems emerged in this review are pointed out and studies are suggested to clarify some controversial points.